The Influence of Resilience And Social Support on Post-Traumatic Stress Disorder (Ptsd) in Early Adults - Syafitri, Sheila Rahmi; Sovitriana, Rilla (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
Many unpleasant events and attached to a person cause trauma for those who experience them. Traumatic experiences in early adulthood can greatly affect a person's personal, emotional, and social development. These traumatic events can be said to be PostTraumatic Stress Disorder (PTSD), which is a mental disorder experienced by individuals who experience traumatic events, which lasts for months or even years after exposure to traumatic events. Resilience and social support are considered to influence a person's vulnerability to PTSD. So, the aim of this research is to see how resilience and social support influence PostTraumatic Stress Disorder (PTSD) in young adults in Jabodetabek. This research is a quantitative study with a sample of 116 early adult respondents in Jabodetabek who had experienced a traumatic event with an age range of 20-40 years. The research results show that resilience and social support have a significant influence on Post-Traumatic Stress Disorder (PTSD) in early adulthood (p<0.001; R2 = 0.406). So it can be concluded that there is an influence of resilience and social support on Post-Traumatic Stress Disorder (PTSD) in early adulthood in Jabodetabek.